Mutually Responsive Orientation: A novel observational assessment of mother-child mealtime interactions. (1st October 2016) - Bergmeier, Heidi; Aksan, Nazan; McPhie, Skye; Fuller-Tyszkiewicz, Matthew; Baur, Louise; Milgrom, Jeannette; Campbell, Karen; Demir, Defne; Skouteris, Helen
Abstract: Mother-child mealtime interactions during preschool years is an important but overlooked factor when evaluating the influence of parent-child relationships on child eating and weight. This paper describes the validation of the Mutually Responsive Orientation (MRO) coding system adapted for assessing parent-child interactions during food preparation and consumption situations. Home-based mealtimes of 94 mothers and their children (3.03 ± 0.75 years) were filmed at two time points, 12-months apart. Filmed dimensions of mutual mother-child responsiveness, shared positive affect, maternal control relating to food and child compliance were assessed. Objective BMI and maternal reports of parenting, feeding, child eating, diet and child temperament were also collected. Correlations, repeated measures ANOVAs and regressions were performed to examine the validity of MRO variables and their stability across both time points. Validation analysis showed the MRO coding system performed as expected: dyads with higher MRO scores expressed lower control/power assertion, lower child non-compliance, and greater committed compliance. The measure demonstrated sensitivity to specific contexts: maternal responsiveness, mother and child positive affect were higher during food consumption compared to food preparation. Coded dimensions were stable across time points, with the exception of decreases in maternal responsiveness in food consumption and child non-compliance in food preparation. MRO and maternal dimensions were correlated with maternally reported parenting and feeding measures. Maternal responsiveness (inversely) and child responsiveness (positively) were concurrently associated with child fussy eating, and child refusal was prospectively and inversely associated with child fussy eating. Findings suggest the adapted MRO coding system is a useful measure for examining observed parent-child mealtime interactions potentially implicated in preschoolers' eating and weight development.